A Construction of Beam Propagation Methods for Optical Waveguides (Communications in Computational Physics, 2009)
This paper presents a systematic method to derive Beam Propagation Modelsfor optical waveguides. The technique is based on the use of the symbolic calculusrules for pseudodifferential operators. The cases of straight and bent optical waveguidesare successively considered.